Effectiveness Of Using Accounting Information Systems At The Perumnas Simalingkar Village Office, Pancur Batu District, Deli Serdang Regency, North Sumatra Province - Adetya Rizki Siregar; Ayu Kurnia Sari; Tia Novira Sucipto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The use of information and communication technology in the digital era is crucial in various sectors, including village government, to improve the efficiency and quality of public services. The Village Information System (SID) is designed to facilitate the management of village data, information, and services to make them more transparent, accountable, and participatory. With the SID, it is hoped that the public will have easier access to village information, and village officials will be able to work more effectively in supporting village development. Research is essentially aimed at demonstrating the truth and solving problems related to what is being studied, which is carried out using a method that is appropriate and relevant to the research objectives. According to (Sugiyono, 2021), a research method is essentially a scientific way to obtain data for specific purposes and uses. A research method is a technique or method of conducting research, related to searching, collecting, and processing data, as well as drawing conclusions or addressing existing problems in a study. To increase effectiveness, regular training for village officials on the use of AIS and basic accounting principles is needed. The development of an online-based system with adequate internet network support. Periodic evaluation of system use to ensure suitability to village needs.